The epistemology: a comprehensive approach from Islamic perspective - Afridi, Muhammad Adil Khan (s.n, 2012)
Islam desires human being to study and acquire knowledge in every possible occasion. The stanzas of the Qur'an grasp, assist, counsel, and inspire people to perceive the miracles of nature, the progression of daylight and nighttime, the engagements of stars, the sun, moon, and other heavenly bodies. One of the distinctive feature of Islam is its emphasis on knowledge. The Qur'an and the Islamic tradition invite Muslims to seek and acquire knowledge and wisdom and to hold men of knowledge in high esteem. However, this study will try to illustrate the necessity and effectiveness of knowledge to be a good believer. Furthermore, it will be also discussing on the philosophical view point on knowledge from the religious thinker as well to promote Islamic education system in compare to the others